Weighing in on a method to discriminate maize haploid from hybrid seed. Issue 3 (31st March 2015) - Smelser, Andrew; Blanco, Michael; Lübberstedt, Thomas; Schechert, Axel; Vanous, Adam; Gardner, Candice; Tuberosa, M.
Abstract The doubled haploid breeding method can produce maize inbred lines faster than traditional methods, but there are challenges associated with it. Sorting haploid from hybrid seed based on visual colour markers is time consuming and can be difficult due to colour inhibitors that obscure pigmentation needed to distinguish between haploid, hybrid and outcrossed seed. In this study, weight was evaluated as a method to sort haploid from hybrid seed. A first experiment utilized two families for analysis in a preliminary study. Eleven haploid and hybrid kernels from both families were weighed for a total of 44 experimental units. A second experiment was carried out using six families, using the same format as the previous, for 132 experimental units. Hybrid seed weighed significantly more than haploid seed in both experiments. However, the interaction between line and kernel type was significant in the second experiment. In conclusion, efficacy of sorting haploid from hybrid kernels based on weight depends on the genotypes involved.